Challenges of developing and conducting clinical trials in rare disorders - Kempf, Lucas; Goldsmith, Jonathan C.; Temple, Robert (American journal of medical genetics. Part A, 2018)
Rare disease drug development is a rapidly expanding field. Clinical researchers in rare diseases face many challenges when conducting trials in small populations. Disease natural history is often poorly understood and the ability to detect clinically meaningful outcomes requires understanding of their rate of occurrence and variability, both of which contribute to difficulties in powering a study. Standard trial designs are not optimized to obtain adequate safety and efficacy data from small numbers of patients, so alternative designs (enrichment, crossover, adaptive, N‐of 1) need to be considered. The affected patients can be hard to identify, especially early in the course of their disease, are generally geographically dispersed, and are often children. Trials are frequently conducted on an international scale and may be subject to complex or multiple regulatory agency oversights and may be affected by local customs, cultures, and practices. A basic understanding of the FDA programs supporting development of drugs for rare diseases is provided by this review and the role of early consultation with the FDA is emphasized. Of recent FDA New Molecular Entities (NME) approvals, 41% (17 approvals) in 2014, 47% (21 approvals) in 2015, and 41% (9 approvals) in 2016 were for rare disease indications. Through effective interactions and collaborations with physicians, institutions, and patient groups, sponsors have been successful in bringing new treatments to market for individuals affected by rare diseases. Challenges to drug development have been overcome through the focused efforts of patients/families, non‐profit patient advocacy groups, drug developers, and regulatory authorities.